International private investment: international economic law - Lowenfeld, Andreas F. (New York : M. Bender, 1982)
Legal issues and the skills to teach Lawyers through a connected series of events. Cases are presented to assist readers on government regulation of foreign investment.
Includes bibliographical references and index.
gp 25/01/2019
Loans
Keywords: Investments, Foreign